Analisis Kebutuhan Media Pembelajaran Berbasis Augmented Reality pada Materi Sistem Pencernaan Manusia Kelas V SD - Fitria Zahrotun Nabila; Sumadi Sumadi; Wendri Wiratsiwi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
This study aims to analyze the need for Augmented Reality (AR)-based learning media for the human digestive system in fifth-grade elementary school. Motivated by the limitations and inability of conventional learning media to visualize abstract concepts, this study uses a qualitative descriptive method through observation, teacher interviews, and student questionnaires. Data analysis is used to identify learning conditions, existing media, and teacher-student needs for interactive learning tools. The results of the study indicate that science learning is still dominated by books, two-dimensional images, and lecture methods, so that students have difficulty understanding abstract concepts. Therefore, it is concluded that AR-based learning media for the human digestive system is needed to present the material more concretely, so that the learning process becomes more active and interactive for fifth-grade elementary school students. This media is expected to be able to increase learning interest, conceptual understanding, and student engagement during the learning process. In addition, the results of the study can be a reference for teachers in developing learning innovations that utilize digital technology according to the characteristics and needs of students in elementary schools.